(untitled) (New York, 2003)
The Standard Handbook of Biomedical Engineering bridges the gap between engineering principles and biological systems. Over 40 experts from universities and medical centers throughout North America and Israel have produced a practical reference for the biomedical professional who is seeking to solve a wide range of engineering and design problems, whether to enhance a diagnostic or therapeutic technique, reduce the cost of manufacturing a medical instrument or prosthetic device, improve the daily life of a patient with a disability, or increase the effectiveness of a hospital department.
Keywords: Biomedical engineering,Medical instruments and apparatus,Kỹ thuật y sinh,Máy móc và dụng cỵu y tế; Design and construction,Thiết kế và xây dựng